Evaluation of treatment and outcomes for Hispanic patients with gastric cancer at Commission on Cancer‐accredited centers in the United States. Issue 7 (11th February 2019) - Zhao, Beiqun; Leichman, Lawrence P.; Horgan, Santiago; Bouvet, Michael; Kelly, Kaitlyn J.
Abstract: Background and Objectives: Gastric cancer in the Hispanic population commonly presents with poor clinical features. Characteristics of this vulnerable population and optimal therapy for these patients have not been clearly defined. Methods: Using the National Cancer Database (2004‐2014), we analyzed patient demographics, clinical factors, treatment‐related factors, and outcomes for Hispanic and non‐Hispanic patients with gastric adenocarcinoma in the United States. Results: A total of 129 666 patients were included in this analysis. Hispanics were younger, more often female, had larger tumors, and were more likely to present with metastatic disease (all P  < 0.001). Hispanics were more likely to undergo staging laparoscopy (5.6% vs 4.9%; P  = 0.037), gastrectomy (63.5% vs 56.9%; P  < 0.001), and ≥ 15 lymph nodes examined (56.1% vs 50.5%; P  < 0.001). Hispanics were less likely to have negative margins (91.2% vs 92.8%; P  = 0.004). Hispanics with stage II/III disease were less likely to receive neoadjuvant therapy (31.7% vs 38.7%; P  < 0.001), but more likely to receive multimodal therapy (48.9% vs 46.1%; P  = 0.01). Predictors for improved overall survival in Hispanics included multimodal therapy, negative margins, and treatment at an academic center. Conclusions: Efforts to optimize treatment of this distinct and growing population of gastric cancer patients should focus on earlier diagnosis, referral to academic centers, and high‐quality surgery.